Combating cancer stem cells: RNA m6A methylation and small-molecule drug discovery - Zhang, Honghai; Wang, Xueer; Chen, Jianjun; Su, Rui (Frontiers in Drug Discovery, 2024)
Cancer stem cells (CSCs) are a small population of less differentiated cells with robust self-renewal ability. CSCs have been recognized as the root cause of tumor initiation, progression, relapse, and drug resistance. Recent studies from us and others have highlighted that N 6 -methyladenosine (m 6 A), the most prevalent modification in mRNA, plays a crucial role in carcinogenesis and CSC homeostasis. Dysregulation of the m 6 A modification machinery has been implicated in CSC survival and self-renewal, thereby regulating cancer progression and therapeutic resistance. In this review, we provide an overview of the roles and molecular mechanisms of the RNA m 6 A modification machinery in CSC survival and self-renewal. Additionally, we summarize the currently known small-molecule inhibitors targeting the dysregulated m 6 A modification machinery and discuss proof-of-concept studies focusing on the efficacy of these compounds in eliminating CSCs and cancers.